Swarm intelligence: problem-solving societies (a review) - Mario A. Muñoz; Jesús A. López; Eduardo F. Caicedo (Ingeniería e Investigación, 2008)
This paper presents a review of the basic concepts of swarm intelligence and some views regarding the future of re-search in this area aimed at establishing a starting point for future work in different engineering fields. A bibliogra-phic search of the most updated databases regarding classic articles on the subject and the most recent applications and results was used for constructing this review, especially in the areas of automatic control, signal and image pro-cessing and robotics. The main concepts were selected and organised in chronological order. A taxonomy was ob-tained for evolutionary computing techniques, a clear differentiation between swarm intelligence and other evolutio-nary algorithms and an overview of the different techniques and applications.